Phytochemical and Pharmacological Investigation of Cissus quadrangularis L. - Sandeep Pandey *; Shikha Parmar; Monika Shukla Shukla; Varsha Sharma Sharma; Akansha Dwivedi; Anamika Pandey; Monika Mishra (Lorestan University of Medical Sciences, 2022)
Traditional system of medicine practiced since time immemorial has emerged as an alternative for modern medicine as it is economical, nature-based and without side effects. Medicinal plant Cissus quadrangularis L. has been used in the Indian system of traditional medicine due to its easier propagation and availability. The phytochemical composition of the plant mainly consists of flavonoids, alkaloids, glycosides, steroids, saponins, tannins, triterpenes, benzenoids, phenols, and total protein. The stem is the most important part of the plant with various therapeutic properties. The plant exhibits anti-arthritis, anti-inflammatory, anti-cancer, antioxidant, antidiabetic, anti-obesity, anti-microbial, anti-hemorrhoidal, anthelmintic, and other pharmacological properties. The plant has traditionally been used in the treatment of broken bones, rheumatic pains, bowel infections, burns, wounds, eye disorders, menstrual disorders, boils, asthma, gastritis, piles hemorrhoids, anemia, and indigestion. This systematic review documented the phytochemical composition of various plant parts along with evaluating research articles for designing the pharmacological application of the plant and its use in drug industries.